Comparative study of perceived learning needs of convalescent patients after heart failure with that of nurses’ perception in selected hospitals of Mumbai - Karadkar, Gargee (International Journal of Nursing Research, 2023)
Heart failure (HF) is a cardiovascular disease of cardinal importance because of several factors: a) an increasing occurrence due to the aging of the population, primary and secondary prevention of cardiovascular events, and modern advances in therapy, b) a bad prognosis: around 65% of patients die within 5 years of diagnosis, c) a high economic cost: HF accounts for 1% to 2% of total health care expenditure. Aim: To compare the perceived learning needs of convalescent patients after heart failure with that of nurses‘ perceptions. Methods: A total no. of 80 participants, which included forty convalescent patients after heart failure and forty staff nurses working in medical wards of the municipal hospital were taken as sample by non-probability purposive sampling. A non– experimental comparative design was used. Structured interview schedule for patients and nurses were used that included age, gender, educational status, marital status, occupation, years of registration, total experience of the nurse, experience in medical wards and attendance to any refresher courses. Results: The perceptions regarding the learning needs of convalescent patients after heart failure and staff nurses need to be valued. The study‘s results have added to the nursing knowledge base that such patients and nurses continue to have medication information as top learning need. But the other learning needs do not match with the other rankings given by the nurses and patients.